Glass ceramic solid electrolyte and preparation method thereof
By using raw materials with a molar ratio of 3:1:y of Li2S, P2S5 and LiSCN, 3Li2S·P2S5·yLiSCN glass ceramic solid electrolyte is prepared by ball milling and heat treatment, which solves the difficulty of upgrading the Li2S-P2S5 binary system in the prior art. The problems of ionic conductivity and maintaining soft and texture properties have achieved a comprehensive effect of high ionic conductivity, low Young's modulus and high energy density.
Patent Information
- Application Number
- CN202411482438.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-07
AI Technical Summary
The existing Li2S-P2S5 binary glass ceramic solid electrolytes are difficult to maintain soft properties and low Young's modulus while improving ionic conductivity, and cannot meet the demand for high-rate performance and safety of all-solid-state batteries to improve energy density.
Li2S, P2S5 and LiSCN with a molar ratio of 3:1:y were used as raw materials, and amorphization reaction was initiated by ball milling, and then heat treatment was performed at 60-200°C to prepare glass ceramic solid electrolyte 3Li2S·P2S5·yLiSCN. This method stabilizes the high-temperature fast ion conductive phase by linear structure SCN-doped lattice, maintains low Young's modulus, and reduces the electrolyte density.
While maintaining the soft quality properties, the room temperature ion conductivity of glass-ceramic solid electrolyte is improved, the density of the electrolyte isolation layer in all-solid state batteries is enhanced, the risk of short-circuiting of the battery under high current density is reduced, and the battery is improved Energy density.
Smart Images

Figure CN119390352A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of solid electrolyte technology, and in particular to a glass ceramic solid electrolyte and a preparation method thereof. Background Art
[0002] Glass-ceramic solid electrolytes are soft and have high electrical conductivity. All-solid-state batteries using them have attracted increasing interest from researchers due to their potential high safety and high specific energy characteristics. A typical example of a glass-ceramic solid electrolyte is Li 2 SP 2 S 5 Binary system, which is a mixture of several crystalline phases and glass phases, including Li3 (PS4), Li4 (P2S7) and Li2 (P2S6) and the so-called thio-LISICON II. The preparation method is to anneal the completely amorphous mixture and crystallize to obtain glass ceramics containing microcrystals. 2- When anion doping is performed, an appropriate amount of Li + Vacancy or interstitial Li + , change the short-term or long-term Li + The transmission path and potential barrier, increase or decrease the lattice energy of the crystal, and strengthen the ionic bond, thereby changing the ion transport properties and lattice stiffness of the fast ion conductor.
[0003] Improve Li 2 SP 2 S 5 Improving the ionic conductivity of binary glass-ceramics while reducing their material modulus is an important current research direction.
[0004] On the one hand, the lattice stiffness of fast ion conductors has a direct impact on the macroscopic hardness and density of electrolyte materials. When external pressure is applied, electrolyte materials with low Young's modulus are more likely to obtain higher compaction density, thereby improving the density of the electrolyte isolation layer in all-solid-state batteries and reducing the risk of short circuits at high current densities. On the other hand, solid electrolytes should also have a certain high lithium ion transmission capacity. Obtaining a high-temperature fast conduction phase, high defect concentration, and low activation energy at room temperature through anion and cation doping is another important research goal.
[0005] Current Li 2 SP 2 S 5 The research on binary glass / glass ceramics has reached a bottleneck: on the one hand, it is necessary to maintain its soft and easy-to-compact properties (Young's modulus <10GPa), and on the other hand, the higher rate performance requirements of the battery put forward higher requirements for the conductivity of the electrolyte (conductivity>3mS / cm). 2 SP 2 S5 Thermal treatment temperature of binary glass or doping with strongly coordinated Cl - / Br - , can not make Li 2 SP 2 S 5 Binary glass-ceramics maintain soft properties while taking into account ionic conductivity, or maintain sufficiently high ionic conductivity while reducing Young's modulus.
[0006] Patent document CN103650231B proposes a glass ceramic material with the chemical formula xLiI·(100-x)(0.75Li2S·0.25P2S5). The component when x=15 is first fully ball-milled to be completely amorphous (glass phase), and then heat-treated at 190°C to obtain a glass ceramic, whose important characteristics are that there are strong peaks at 2θ=20.0° and 23.6° in the XRD spectrum (the so-called thio-LISICONII phase), and very weak diffraction peaks at 2θ=21.1° and 28.0° (the so-called Li4PS4I phase), and the highest room temperature conductivity is 3.4mS / cm. Similarly, the non-patent literature Investigation of the Suppression of Dendritic Lithium Growth with a Lithium-Iodide-Containing Solid Electrolyte proposes a component with a chemical formula of 70Li3PS4·30LiI, whose amorphous Young's modulus is only 8.5GPa and the conductivity is about 1mS / cm; after the amorphous material is heat treated at 200℃, the room temperature conductivity of the highest ionic conductivity glass-ceramic material is 3.2mS / cm, and the corresponding Young's modulus is about 17GPa. If the heat treatment temperature is further increased to above 400℃ in order to obtain higher ionic conductivity, the material undergoes a phase change, from glass ceramic to ceramic phase, and the low ionic conductivity Li4PS4I phase and Li7PS6 will appear, and the conductivity will decrease significantly (~10 -5 S / cm). Summary of the invention
[0007] The present application provides a glass ceramic solid electrolyte and a preparation method thereof. The prepared glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 yLiSCN has low density and can maintain its soft properties while taking into account high ionic conductivity, which helps to improve the energy density of all-solid-state batteries.
[0008] In one aspect, the present application provides a method for preparing a glass ceramic solid electrolyte, the method comprising:
[0009] Weigh Li and Mg according to the molar ratio of 3:1:y. 2 S.P. 2 S 5 , LiSCN, to obtain a raw material for preparation; wherein y is in the range of 0.1-0.55;
[0010] The raw materials, dispersion medium and ball milling balls are placed in a ball milling jar for ball milling to induce an amorphization reaction to obtain an intermediate product; wherein the ball milling speed corresponding to the ball milling treatment is 300-600 rpm and the ball milling time is 10-60 hours;
[0011] The intermediate product is heat treated at 60-200° C. for 1.1-55 hours to obtain the glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 ·yLiSCN.
[0012] Furthermore, the preparation raw materials, dispersion medium and ball milling balls are placed in a ball milling tank for ball milling to induce an amorphization reaction to obtain an intermediate product, including:
[0013] The raw material, the dispersion medium and the ball milling balls are placed in the ball milling jar for ball milling treatment to induce the amorphization reaction, thereby obtaining a mixture of the ball milling balls and the intermediate product; the dispersion medium comprises one or more of saturated carbon chain hydrocarbons and benzene organic liquids; the mass ratio of the raw material, the dispersion medium and the ball milling balls is 1:(0-50):(1-50);
[0014] The mixture of the ball milling balls and the intermediate product is separated to obtain the intermediate product.
[0015] Further, the preparation raw material, the dispersion medium and the ball milling balls are placed in the ball milling jar for ball milling to induce the amorphization reaction to obtain a mixture of the ball milling balls and the intermediate product, including:
[0016] Placing the preparation raw material, the dispersion medium and the ball milling balls in the ball milling jar for ball milling to initiate the amorphization reaction and obtain a mixture of the ball milling balls and the initial intermediate product;
[0017] Using Cu-Kα line as X-ray source to test the initial intermediate product, and obtaining the test result of the initial intermediate product;
[0018] If the test result of the initial intermediate product indicates that the initial intermediate product is amorphous, the initial intermediate product is determined to be an intermediate product, and a mixture of the ball milling balls and the intermediate product is obtained.
[0019] Further, the intermediate product is subjected to heat treatment at 60-200° C. for 1.1-55 hours to obtain the glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 yLiSCN, including;
[0020] The intermediate product is placed at a first preset temperature for a heat treatment to obtain an initial product; the first preset temperature range is 60-90° C., and the time corresponding to the heat treatment is 1-5 hours;
[0021] The initial product is placed at a second preset temperature for secondary heat treatment to obtain the glass ceramic solid electrolyte; the second preset temperature range is 100-200° C., and the time corresponding to the secondary heat treatment is 0.1-50 hours.
[0022] Furthermore, the initial product is placed at a second preset temperature for secondary heat treatment to obtain the glass ceramic solid electrolyte, comprising:
[0023] Placing the initial product at the second preset temperature for the secondary heat treatment to obtain the secondary heat treated product;
[0024] Using Cu-Kα rays as an X-ray source to test the product of the secondary heat treatment to obtain a test result of the product of the secondary heat treatment;
[0025] According to the test result of the product of the secondary heat treatment, it is determined whether the peaks of the product of the secondary heat treatment at 2θ=20° and 2θ=21° meet the preset conditions.
[0026] Further, the determining, according to the test result of the product of the secondary heat treatment, whether the peaks of the product of the secondary heat treatment at 2θ=20° and 2θ=21° meet the preset conditions comprises:
[0027] If it is determined that the peaks of the product of the secondary heat treatment at 2θ=20° and 2θ=21° meet the preset conditions, then the product of the secondary heat treatment is determined to be the glass ceramic solid electrolyte;
[0028] If it is determined that the peaks of the product of the secondary heat treatment at 2θ=20° and 2θ=21° do not meet the preset conditions, continue the secondary heat treatment until the peaks of the product at 2θ=20° and 2θ=21° meet the preset conditions.
[0029] Furthermore, the glass ceramic solid electrolyte is formed by stacking a plurality of spherical glass ceramic solid electrolyte particles, and the particle size of the glass ceramic solid electrolyte particles ranges from 0.5 to 3 μm;
[0030] The glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 yLiSCN includes one or more of glass and glass ceramic.
[0031] Furthermore, the glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 In the diffraction measurement of yLiSCN using Cu-Kα line as the X-ray source, the peak intensity ratio at 2θ=20° / 2θ=21° ranges from 1.65 to 2.05.
[0032] On the other hand, a glass ceramic solid electrolyte is provided. The glass ceramic solid electrolyte is prepared by the above-mentioned preparation method.
[0033] On the other hand, an all-solid-state battery is provided, which includes a composite positive electrode layer, a composite negative electrode layer and an isolation layer; at least one of the composite positive electrode layer, the composite negative electrode layer and the isolation layer includes the above-mentioned glass ceramic solid electrolyte.
[0034] The glass ceramic solid electrolyte and the preparation method thereof provided in this application have the following technical effects:
[0035] In this application, Li was weighed according to the molar ratio of 3:1:y. 2 S.P. 2 S 5 , LiSCN, to obtain a raw material for preparation; wherein the range of y is 0.1-0.55; placing the raw material for preparation, the dispersion medium and the ball milling ball in a ball milling jar for ball milling treatment to induce an amorphization reaction to obtain an intermediate product; wherein the ball milling speed corresponding to the ball milling treatment is 300-600rpm, and the ball milling time is 10-60h; heat treating the intermediate product to obtain the glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 ·yLiSCN. This application can prepare a glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 yLiSCN, which can maintain soft properties while taking into account high ionic conductivity, uses LiSCN as one of the raw materials, and the linear structure of SCN - It can be doped into the lattice to make the high-temperature fast ion conduction phase (high-temperature phase) more stable at room temperature, which relatively improves the room-temperature ionic conductivity of glass ceramics; LiSCN doped with 3Li 2 S.P. 2 S5 The material maintains a lower Young's modulus, which helps to improve the density of the electrolyte isolation layer in the all-solid-state battery and effectively reduce the short-circuit risk of the battery at high current density; 3Li 2 S.P. 2 S 5 yLiSCN electrolyte has lower density, which helps to improve the energy density of all-solid-state batteries. In addition, there are no halogen atoms such as Cl / Br / I in the raw materials, which will not corrode the current collector. The raw materials are cheap and the heat treatment temperature is lower, which is conducive to large-scale production.
[0036] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions and advantages of the embodiments of this specification or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 It is a schematic flow chart of a method for preparing a glass ceramic solid electrolyte provided in an embodiment of this specification;
[0039] Figure 2 This is a schematic diagram of a LiSCN crystal structure provided in the embodiments of this specification;
[0040] Figure 3 This is a schematic diagram of a process for preparing an intermediate product provided in the examples of this specification;
[0041] Figure 4 This is a schematic diagram of a process for obtaining a mixture of ball milling balls and intermediate products provided in an embodiment of this specification;
[0042] Figure 5 It is a schematic diagram of a heat treatment process provided in an embodiment of this specification;
[0043] Figure 6 It is a schematic diagram of a secondary heat treatment process provided in the embodiments of this specification;
[0044] Figure 7 This is a flow chart of a method for determining whether to terminate the secondary heat treatment according to the test results provided in the embodiment of this specification;
[0045] Figure 8 It is a glass ceramic state 3Li provided in the embodiment of this specification 2S.P. 2 S 5 Scanning electron microscope image of yLiSCN;
[0046] Fig. 9 This is a schematic diagram of an all-solid-state battery structure provided in an embodiment of this specification;
[0047] Fig.10 It is a glass-state 3Li provided in the embodiment of this specification. 2 S.P. 2 S 5 · XRD diffraction pattern of yLiSCN, y=0.5;
[0048] Fig.11 It is a glass-ceramic state 3Li provided in the embodiment of this specification. 2 S.P. 2 S 5 · XRD diffraction pattern of yLiSCN, y=0.5;
[0049] Fig.12 It is a glass-ceramic state 3Li provided in the embodiment of this specification. 2 S.P. 2 S 5 · XRD diffraction pattern of yLiSCN, y=0.05;
[0050] Fig.13 This is a 3Li annealed at 300°C provided in the embodiment of this specification. 2 S.P. 2 S 5 · XRD diffraction pattern of yLiSCN, y=0.5;
[0051] Fig.14 It is a glass-ceramic state 3Li provided in the embodiment of this specification. 2 S.P. 2 S 5 ·XRD diffraction pattern of yLiI, y=0.5. DETAILED DESCRIPTION
[0052] The following will be combined with the drawings in the embodiments of this specification to clearly and completely describe the technical solutions in the embodiments of this specification. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0053] The following is a preparation method of a glass ceramic solid electrolyte of the present application, specifically as follows Figure 1 As shown, the method may include:
[0054] S1: weigh Li and Mg in a molar ratio of 3:1:y. 2 S.P. 2 S 5 , LiSCN, to obtain the preparation raw material; wherein, the range of y is 0.1-0.55.
[0055] In the examples of the present application, Li and 2 S.P. 2 S 5 , LiSCN, as the raw material for preparation, wherein y is in the range of 0.1-0.55, preferably 0.5.
[0056] In the examples of the present application, LiSCN is used as one of the raw materials. - The ionic radius (217 pm) and I - The radius (220 pm) is basically the same, but SCN - P 5 + The binding is tighter, so the linear structure of SCN - The incorporation of 3Li into the lattice makes the high-temperature fast ion conduction phase (high-temperature phase) more stable at room temperature, which relatively improves the room-temperature ionic conductivity of glass ceramics. In addition, compared with LiBr (823K) and LiI (732K), LiSCN has a lower melting point of 547K. 2 S.P. 2 S 5 The resulting material can maintain a lower Young's modulus, which helps to improve the density of the electrolyte isolation layer in the all-solid-state battery and reduce the risk of short circuits at high current densities. In addition, LiSCN has a molecular weight of 65g / mol, which is lower than LiBr (86.9g / mol) and LiI (133.9g / mol), and can produce a lower-density solid electrolyte, which helps to improve the energy density of all-solid-state batteries.
[0057] In the embodiments of the present application, Figure 2 Schematic diagram of the LiSCN crystal structure. LiSCN is chemically and structurally similar to lithium iodide, both of which have large polarizable anions.
[0058] In the embodiment of the present application, the LiSCN in the raw material can be LiSCN·xH 2 O, x is a positive number.
[0059] The present application embodiment is in Li 2 SP 2 S 5Introducing LiSCN with a low melting point and molecular weight into the binary system electrolyte can enable the resulting material to maintain a lower Young's modulus, which helps to increase the density of the electrolyte isolation layer in the all-solid-state battery, and can obtain a solid electrolyte with a lower density, which helps to increase the energy density of the all-solid-state battery; moreover, the raw materials do not contain halogen atoms such as Cl / Br / I, will not corrode the current collector, are stable to the metallic lithium negative electrode, and can remain stable even at low potentials; the raw materials are inexpensive, which is conducive to large-scale production.
[0060] S2: placing the raw materials, dispersion medium and ball milling balls in a ball milling jar for ball milling to induce an amorphization reaction and obtain an intermediate product; wherein the ball milling speed corresponding to the ball milling treatment is 300-600 rpm, and the ball milling time is 10-60 h.
[0061] Furthermore, if Figure 3 As shown, the preparation raw materials, dispersion medium and ball milling balls are placed in a ball milling jar for ball milling to induce an amorphization reaction to obtain an intermediate product, including:
[0062] S21: placing the raw material, the dispersion medium and the ball milling balls in the ball milling jar for ball milling treatment to initiate the amorphization reaction and obtain a mixture of the ball milling balls and the intermediate product; the dispersion medium comprises one or more of saturated carbon chain hydrocarbons and benzene organic liquids; the mass ratio of the raw material, the dispersion medium and the ball milling balls is 1:(0-50):(1-50);
[0063] S22: separating the mixture of the ball milling balls and the intermediate product to obtain the intermediate product.
[0064] In an embodiment of the present application, the three weighed raw materials, dispersion medium and ball milling balls are placed in a ball milling jar, and an amorphization reaction is induced under high-speed ball milling to obtain a mixture of ball milling balls and intermediate products. The mixture of ball milling balls and intermediate products is separated using a sieve to obtain an intermediate product.
[0065] In an embodiment of the present application, the dispersion medium may include one or more of saturated carbon chain hydrocarbons and benzene-based organic liquids. The mass ratio of the preparation raw material to the dispersion medium may be within the range of 1:(0-50), preferably 1:1; the mass ratio of the preparation raw material to the ball milling balls may be within the range of 1:(1-50), preferably 1:30.
[0066] In the embodiments of the present application, the intermediate product is preferably in a glassy state.
[0067] The embodiment of the present application induces an amorphization reaction through ball milling, which can transform the crystalline state into the amorphous state, thereby obtaining an amorphous intermediate product.
[0068] Furthermore, if Figure 4 As shown, the preparation raw material, the dispersion medium and the ball milling balls are placed in the ball milling jar for ball milling to induce the amorphization reaction to obtain a mixture of the ball milling balls and the intermediate product, including:
[0069] S211: placing the preparation raw material, the dispersion medium and the ball milling balls in the ball milling jar for ball milling to induce the amorphization reaction, thereby obtaining a mixture of the ball milling balls and the initial intermediate product;
[0070] S212: using Cu-Kα rays as an X-ray source to test the initial intermediate product to obtain a test result of the initial intermediate product;
[0071] S213: If the test result of the initial intermediate product indicates that the initial intermediate product is amorphous, the initial intermediate product is determined to be an intermediate product, and a mixture of the ball milling balls and the intermediate product is obtained.
[0072] In an embodiment of the present application, after high-speed ball milling induces an amorphization reaction, it is necessary to use Cu-Kα rays as X-rays to test the product after high-speed ball milling. When the test results show that the product after high-speed ball milling is completely amorphous, that is, there is no peak in the XRD test graph, it indicates that amorphization has been completed, and the ball milling treatment can be terminated to obtain an intermediate product; if there are still peaks in the XRD test graph, it indicates that amorphization is not complete, and it is necessary to continue the ball milling treatment, and test the product obtained after the second ball milling treatment until the amorphization is completed and the intermediate product is obtained.
[0073] The embodiment of the present application can obtain information on the progress of the amorphization reaction by performing XRD testing on the amorphization product, thereby ensuring that the amorphization is complete and obtaining a completely amorphous intermediate product.
[0074] S3: heat treating the intermediate product at 60-200° C. for 1.1-55 h to obtain the glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 ·yLiSCN.
[0075] Furthermore, if Figure 5 As shown, the intermediate product is heat treated at 60-200°C for 1.1-55h to obtain the glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 yLiSCN, including;
[0076] S31: placing the intermediate product at a first preset temperature for a heat treatment to obtain an initial product; the first preset temperature range is 60-90° C., and the time corresponding to the first heat treatment is 1-5 hours;
[0077] S32: placing the initial product at a second preset temperature for secondary heat treatment to obtain the glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 ·yLiSCN; the second preset temperature range is 100-200°C, and the time corresponding to the secondary heat treatment is 0.1-50h.
[0078] In the embodiment of the present application, the intermediate product is placed at a first preset temperature for a heat treatment, and the dispersion medium in the intermediate product is separated to obtain an initial product; wherein the first preset temperature range is 60-90°C, and the time corresponding to the first heat treatment is 1-5h; the first heat treatment is preferably performed at 60°C for 2h. Subsequently, the initial product is placed at a second preset temperature for a second heat treatment to obtain the final glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 ·yLiSCN; wherein the second preset temperature range is 100-200°C, the time corresponding to the secondary heat treatment is 0.1-50h, and the secondary heat treatment is preferably performed at 150°C for 3h.
[0079] In the embodiment of the present application, the temperature ranges of the two heat treatments are 60-90°C and 100-200°C, respectively. Compared with the existing heat treatment temperature, the heat treatment temperature provided in the embodiment of the present application is relatively lower, which is conducive to the large-scale production of materials.
[0080] The present embodiment can effectively separate the dispersion medium through two heat treatments to avoid the generation of by-products, and finally obtain a glass-ceramic solid electrolyte 3Li 2 S.P. 2 S 5 ·yLiSCN.
[0081] Furthermore, if Figure 6 As shown, the initial product is placed at a second preset temperature for secondary heat treatment to obtain the glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 yLiSCN, including:
[0082] S321: placing the initial product at the second preset temperature to perform the secondary heat treatment to obtain the secondary heat treated product;
[0083] S322: using Cu-Kα rays as an X-ray source to test the product of the secondary heat treatment, and obtaining a test result of the product of the secondary heat treatment;
[0084] S323: Determine, based on the test result of the product of the secondary heat treatment, whether the peaks of the product of the secondary heat treatment at 2θ=20° and 2θ=21° meet preset conditions.
[0085] In the embodiment of the present application, after the secondary heat treatment, the product of the secondary heat treatment needs to be tested. The test uses Cu-Kα line as the X-ray source to obtain the XRD spectrum of the secondary heat treatment product, and the peaks in the XRD spectrum are observed. Whether the secondary heat treatment is completed is judged based on whether a peak appears in the XRD spectrum and the position and intensity of the peak.
[0086] The embodiment of the present application monitors the process of the secondary heat treatment by XRD test. Through the XRD test spectrum, more accurate crystal state information of the secondary heat treatment product can be obtained, so as to judge whether the secondary heat treatment needs to be terminated according to the crystal state information of the secondary heat treatment product, so as to ensure that the solid electrolyte 3Li in glass ceramic state is obtained. 2 S.P. 2 S 5 ·yLiSCN.
[0087] Furthermore, if Figure 7 As shown, the step of determining whether the peaks of the product of the secondary heat treatment at 2θ=20° and 2θ=21° meet preset conditions according to the test results of the product of the secondary heat treatment comprises:
[0088] S3231: If it is determined that the peaks of the product of the secondary heat treatment at 2θ=20° and 2θ=21° meet preset conditions, then the product of the secondary heat treatment is determined to be the glass ceramic solid electrolyte;
[0089] S3232: If it is determined that the peaks of the product of the secondary heat treatment at 2θ=20° and 2θ=21° do not meet the preset conditions, continue the secondary heat treatment until the peaks of the product at 2θ=20° and 2θ=21° meet the preset conditions.
[0090] In the embodiment of the present application, if the XRD spectrum of the secondary heat treatment product has peaks at 2θ=20° and 2θ=21° (or other positions where peaks should appear theoretically) and reaches a certain intensity, it is determined that the product obtained after the secondary heat treatment is a glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5·yLiSCN; If the XRD spectrum of the secondary heat treatment product does not show a peak or does not reach the appropriate intensity, continue the secondary heat treatment and continue the XRD test until the XRD spectrum meets the conditions to obtain the final product glass ceramic solid electrolyte, ensuring 3Li 2 S.P. 2 S 5 yLiSCN is in glass ceramic state.
[0091] The present invention uses XRD to characterize the product obtained by the secondary heat treatment in a timely manner to ensure that the electrolyte 3Li in a glass-ceramic state is obtained. 2 S.P. 2 S 5 yLiSCN can maintain softness while achieving high ionic conductivity.
[0092] Furthermore, the glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 yLiSCN is composed of a plurality of spherical glass ceramic solid electrolyte particles, the particle size of which ranges from 0.5 to 3 μm.
[0093] The glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 yLiSCN includes one or more of glass and glass ceramic.
[0094] In the present embodiment, 3Li 2 S.P. 2 S 5 yLiSCN does not contain argyrodite structure and polysulfide bonds. The temperature and time of the heat treatment provided in the embodiment of the present application can avoid the generation of the above-mentioned by-products and obtain 3Li in glass-ceramic state. 2 S.P. 2 S 5 ·yLiSCN.
[0095] In the embodiments of the present application, Figure 8 It is 3Li 2 S.P. 2 S 5 SEM images of yLiSCN, such as Figure 8 As shown. Glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 yLiSCN is composed of a plurality of spherical glass-ceramic solid electrolyte particles. The glass-ceramic solid electrolyte particles are irregular smooth particles with a particle size range of 0.5-3μm.
[0096] 3Li in the embodiments of this application 2 S.P. 2 S 5 yLiSCN is composed of multiple glass-ceramic solid electrolyte particles with smaller particle sizes, which can effectively promote ion transport and improve the ionic conductivity of the glass-ceramic solid electrolyte.
[0097] Furthermore, the glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 In the diffraction measurement of yLiSCN using Cu-Kα line as the X-ray source, the peak intensity ratio at 2θ=20° / 2θ=21° ranges from 1.65 to 2.05.
[0098] The present invention uses XRD test to obtain 3Li 2 S.P. 2 S 5 The peak intensity ratio of yLiSCN at 2θ=20° / 2θ=21° is in the range of 1.65-2.05, ensuring that the obtained 3Li 2 S.P. 2 S 5 yLiSCN is in a glass-ceramic state, which can maintain its soft properties while also achieving high ionic conductivity.
[0099] The preparation method provided in the embodiment of the present application can prepare a glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 yLiSCN, which can maintain soft properties while taking into account high ionic conductivity, uses LiSCN as one of the raw materials, and the linear structure of SCN - It can be doped into the lattice to make the high-temperature fast ion conduction phase (high-temperature phase) more stable at room temperature, which relatively improves the room-temperature ionic conductivity of glass ceramics; LiSCN doped with 3Li 2 S.P. 2 S 5 The material maintains a lower Young's modulus, which helps to improve the density of the electrolyte isolation layer in the all-solid-state battery and effectively reduce the short-circuit risk of the battery at high current density; 3Li 2 S.P. 2 S 5 yLiSCN electrolyte has lower density, which helps to improve the energy density of all-solid-state batteries. In addition, there are no halogen atoms such as Cl / Br / I in the raw materials, which will not corrode the current collector. The raw materials are cheap and the heat treatment temperature is lower, which is conducive to large-scale production.
[0100] The present application also provides an all-solid-state battery, the all-solid-state battery comprising a composite positive electrode layer, a composite negative electrode layer and an isolation layer; at least one of the composite positive electrode layer, the composite negative electrode layer and the isolation layer comprises the above-mentioned glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 ·yLiSCN.
[0101] In the embodiment of the present application, the composite positive electrode layer includes a positive electrode active material and an electrolyte, the composite negative electrode layer includes a negative electrode active material and an electrolyte, and the isolation layer is located between the positive and negative electrodes and is an electrolyte layer.
[0102] In the embodiments of the present application, Fig. 9 is a schematic diagram of an all-solid-state battery structure provided in an embodiment of the present application, such as Fig. 9 As shown, the all-solid-state battery includes a positive electrode, a negative electrode, a negative electrode side electrolyte and a positive electrode side electrolyte; wherein at least one of the positive electrode, the negative electrode, the positive electrode side electrolyte and the positive electrode side electrolyte comprises the glass ceramic solid electrolyte 3Li provided in the embodiment of the present application 2 S.P. 2 S 5 ·yLiSCN.
[0103] In the embodiment of the present application, the positive electrode active material may include: rock salt layer type active material, such as LiCoO 2 、LiMnO 2 、LiNiO 2 、LiVO 2 or Li 1+x Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 ; Spinel active materials, such as LiMn 2 O 4 Or Li(Ni 0.5 Mn 1.5 ) 4 ; Inverse spinel active materials, such as LiNiVO 4 or LiCoVO 4 ; Olivine-type active materials, such as LiFePO 4 、LiMnPO 4 、LiCoPO 4 or LiNiPO 4 ; Silicon-containing active materials, such as Li 2 FeSiO 4 or Li 2 MnSiO; rock salt layer type active materials where part of the transition metal is replaced by a foreign metal, such as LiNi 0.8 Co (0.2-x)Al x O 2 (0<x<0.2); spinel active materials in which a portion of transition metals are replaced by heterogeneous metals, such as Li 1+x Mn 2-x-y M y O 4 (wherein M includes at least one of Al, Mg, Co, Fe, Ni, and Zn, and 0<x+y<2); and lithium titanate, such as Li 4 Ti 5 O 12 ; and sulfide positive electrode active materials, including: copper sulfide, iron sulfide, cobalt sulfide, nickel sulfide, etc.
[0104] In an embodiment of the present application, the negative electrode active material may include: a metal material, a carbon material, an oxide, a nitride, a tin compound or a silicon compound, etc. The metal material may be a single metal material or an alloy. Examples of metal materials are lithium metal or lithium alloys. Examples of carbon materials are natural graphite, coke, graphitizable carbon, carbon fiber, spherical carbon, artificial graphite or amorphous carbon, etc. From the perspective of capacity density, suitable examples of negative electrode active materials are silicon (i.e., Si), tin (i.e., Sn), silicon compounds or tin compounds.
[0105] In the present embodiment, in addition to 3Li 2 S.P. 2 S 5 In addition to yLiSCN, the solid electrolyte in the composite positive electrode layer, composite negative electrode layer, and isolation layer may include Li 3 YC 6 , Li 3 InCl 6 , Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -LiBr, Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are positive numbers, and Z is one of Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (where x and y are positive numbers, and M is one of P, Si, Ge, B, Al, Ga, and In), Li 10 G 2 S 12 Preferably, the composite negative electrode layer and the isolation layer close to the negative electrode contain 3Li 2 S.P. 2 S 5 ·yLiSCN.
[0106] Embodiment 1:
[0107] This embodiment provides a glass ceramic solid electrolyte and a preparation method thereof, and the specific preparation method includes:
[0108] Weigh Li according to the molar ratio of 3:1:0.5 2 S.P. 2 S 5 , LiSCN raw materials 13.75g, 22.23g, 3.25g, to obtain 39.23g of preparation raw materials;
[0109] 39.23 g of the raw material, 39.23 g of the dispersion medium n-heptane and 784.6 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and milled at 400 rpm for 20 h to induce an amorphization reaction to obtain an intermediate product, namely glassy 3Li 2 S.P. 2 S 5 0.5LiSCN;
[0110] The intermediate product was subjected to two-step heat treatment at 60℃-2h and 150℃-3h to obtain the glass-ceramic solid electrolyte 3Li 2 S.P. 2 S 5 0.5LiSCN.
[0111] Embodiment 2:
[0112] This embodiment provides a glass ceramic solid electrolyte and a preparation method thereof, and the specific preparation method includes:
[0113] Weigh Li according to the molar ratio of 3:1:0.1 2 S.P. 2 S 5 , LiSCN raw materials 13.75g, 22.23g, 0.65g, to obtain 36.63g of preparation raw materials;
[0114] 36.63 g of the raw material, 36.63 g of the dispersion medium n-heptane and 732.6 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and milled at 400 rpm for 20 h to induce an amorphization reaction to obtain an intermediate product, namely glassy 3Li 2 S.P. 2 S 5 0.5LiSCN;
[0115] The intermediate product was subjected to two-step heat treatment at 60℃-2h and 150℃-3h to obtain the glass-ceramic solid electrolyte 3Li 2 S.P. 2 S 5 0.5LiSCN.
[0116] Embodiment 3:
[0117] This embodiment provides a glass ceramic solid electrolyte and a preparation method thereof, and the specific preparation method includes:
[0118] Weigh Li according to the molar ratio of 3:1:0.55 2 S.P. 2 S 5 , LiSCN raw materials 13.75g, 22.23g, 3.575g, to obtain 39.555g of preparation raw materials;
[0119] 39.555 g of the raw material, 39.555 g of the dispersion medium n-heptane and 791.1 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and milled at 400 rpm for 20 h to induce an amorphization reaction to obtain an intermediate product, namely glassy 3Li 2 S.P. 2 S 5 0.5LiSCN;
[0120] The intermediate product was subjected to two-step heat treatment at 60℃-2h and 150℃-3h to obtain the glass-ceramic solid electrolyte 3Li 2 S.P. 2 S 5 0.5LiSCN.
[0121] Embodiment 4:
[0122] This embodiment provides a glass ceramic solid electrolyte and a preparation method thereof, and the specific preparation method includes:
[0123] Weigh Li according to the molar ratio of 3:1:0.5 2 S.P. 2 S 5 、LiSCN·H 2 O raw materials 13.75g, 22.23g, 4.15g each, to obtain 40.13g of preparation raw materials;
[0124] 40.13 g of the raw material, 40.13 g of the dispersion medium n-heptane and 802.6.6 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and milled at 400 rpm for 20 h to induce an amorphization reaction to obtain an intermediate product, namely glassy 3Li 2 S.P. 2 S 5 0.5LiSCN;
[0125] The intermediate product was subjected to two-step heat treatment at 60℃-2h and 150℃-3h to obtain the glass-ceramic solid electrolyte 3Li 2 S.P. 2 S 5 0.5LiSCN.
[0126] Comparative Example 1:
[0127] This comparative example provides a glass ceramic solid electrolyte and a preparation method thereof, and the specific preparation method includes:
[0128] Weigh Li according to the molar ratio of 3:1:0.05 2 S.P. 2 S 5, LiSCN raw materials 13.75g, 22.23g, 0.325g, to obtain 36.305g of preparation raw materials;
[0129] 36.305 g of the raw material, 36.305 g of the dispersion medium n-heptane and 726.1 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and milled at 400 rpm for 20 h to induce an amorphization reaction to obtain an intermediate product, namely glassy 3Li 2 S.P. 2 S 5 0.5LiSCN;
[0130] The intermediate product was subjected to two-step heat treatment at 60℃-2h and 150℃-3h to obtain the glass-ceramic solid electrolyte 3Li 2 S.P. 2 S 5 0.5LiSCN.
[0131] Comparative Example 2:
[0132] This comparative example provides a glass ceramic solid electrolyte and a preparation method thereof, and the specific preparation method includes:
[0133] Weigh Li according to the molar ratio of 3:1:0.6 2 S.P. 2 S 5 , LiSCN raw materials 13.75g, 22.23g, 3.9g, to obtain 39.88g of preparation raw materials;
[0134] 39.88 g of the raw material, 39.88 g of the dispersion medium n-heptane and 797.6 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and milled at 400 rpm for 20 h to induce an amorphization reaction to obtain an intermediate product, namely glassy 3Li 2 S.P. 2 S 5 0.5LiSCN;
[0135] The intermediate product was subjected to two-step heat treatment at 60℃-2h and 150℃-3h to obtain the glass-ceramic solid electrolyte 3Li 2 S.P. 2 S 5 0.5LiSCN.
[0136] Comparative Example 3:
[0137] This comparative example provides a glass ceramic solid electrolyte and a preparation method thereof, and the specific preparation method includes:
[0138] Weigh Li according to the molar ratio of 3:1:0.5 2 S.P.2 S 5 , LiSCN raw materials 13.75g, 22.23g, 3.25g, to obtain 39.23g of preparation raw materials;
[0139] 39.23 g of the raw material, 39.23 g of the dispersion medium n-heptane and 784.6 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and milled at 400 rpm for 20 h to induce an amorphization reaction to obtain an intermediate product, namely, glass-ceramic 3Li 2 S.P. 2 S 5 0.5LiSCN;
[0140] The intermediate product was subjected to two-step heat treatment at 60℃-2h and 150℃-3h to obtain glass-ceramic 3Li 2 S.P. 2 S 5 0.5LiSCN.
[0141] Comparative Example 4:
[0142] This comparative example provides a glass ceramic solid electrolyte and a preparation method thereof, and the specific preparation method includes:
[0143] Weigh Li according to the molar ratio of 3:1:0.5 2 S.P. 2 S 5 , LiSCN raw materials 13.75g, 22.23g, 3.25g, to obtain 39.23g of preparation raw materials;
[0144] 39.23 g of the raw material, 39.23 g of the dispersion medium n-heptane and 784.6 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and milled at 400 rpm for 20 h to induce an amorphization reaction to obtain an intermediate product, namely glassy 3Li 2 S.P. 2 S 5 0.5LiSCN;
[0145] The intermediate product was subjected to two-step heat treatment at 60℃-2h and 300℃-3h to obtain the glass-ceramic solid electrolyte 3Li 2 S.P. 2 S 5 0.5LiSCN.
[0146] Comparative Example 5:
[0147] This comparative example provides a glass ceramic solid electrolyte and a preparation method thereof, and the specific preparation method includes:
[0148] Weigh Li according to the molar ratio of 3:1:0.5 2 S.P. 2 S 5 , LiSCN raw materials 13.75g, 22.23g, 3.25g, to obtain 39.23g of preparation raw materials;
[0149] 39.23 g of the raw material, 39.23 g of the dispersion medium n-heptane and 784.6 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and milled at 400 rpm for 20 h to induce an amorphization reaction to obtain an intermediate product, namely glassy 3Li 2 S.P. 2 S 5 0.5LiSCN;
[0150] The intermediate product was subjected to two-step heat treatment at 60℃-2h and 100℃-3h to obtain the glass-ceramic solid electrolyte 3Li 2 S.P. 2 S 5 0.5LiSCN.
[0151] Comparative Example 6:
[0152] This comparative example provides a glass ceramic solid electrolyte and a preparation method thereof, and the specific preparation method includes:
[0153] Weigh Li according to the molar ratio of 3:1:0.5 2 S.P. 2 S 5 , LiI raw materials 13.75g, 22.23g, 6.695g, to obtain 42.675g of preparation raw materials;
[0154] 42.675 g of the raw material, 42.675 g of the dispersion medium n-heptane and 853.5 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and milled at 400 rpm for 20 h to induce an amorphization reaction to obtain an intermediate product, namely glassy 3Li 2 S.P. 2 S 5 0.5LiI;
[0155] The intermediate product was subjected to two-step heat treatment at 60℃-2h and 150℃-3h to obtain the glass-ceramic solid electrolyte 3Li 2 S.P. 2 S 5 ·0.5LiI.
[0156] In the examples of the present application, the difference between Example 2 and Example 1 is that y=0.10, and the other conditions are the same as those of Example 1; the difference between Example 3 and Example 1 is that y=0.55, and the other conditions are the same as those of Example 1; the difference between Example 4 and Example 1 is that LiSCN·H 2 O instead of LiSCN is used as one of the raw materials, and the other conditions are the same as in Example 1; the difference between Comparative Example 1 and Example 1 is that y=0.05, and the other conditions are the same as in Example 1; the difference between Comparative Example 2 and Example 1 is that y=0.05, and the other conditions are the same as in Example 1; the difference between Comparative Example 3 and Example 1 is that the intermediate product is in a glass-ceramic state, and the other conditions are the same as in Example 1; the difference between Comparative Example 4 and Example 1 is that the heat treatment temperatures are 60°C-2h and 300°C-3h, and the other conditions are the same as in Example 1; the difference between Comparative Example 5 and Example 1 is that the heat treatment temperatures are 60°C-2h and 100°C-3h, and the other conditions are the same as in Example 1; the difference between Comparative Example 6 and Example 1 is that the raw material LiSCN is replaced with LiI, and the other conditions are the same as in Example 1.
[0157] In the examples of the present application, the glass ceramic solid electrolytes prepared in the above examples and comparative examples were subjected to XRD test, conductivity test, all-solid-state battery test and Young's modulus test.
[0158] In the examples of the present application, the XRD test method is as follows: in an argon atmosphere, an X-ray diffraction device is used to measure the X-ray diffraction patterns of the solid electrolyte materials of some examples and comparative examples, using Cu-Kα rays as the X-ray source.
[0159] In the embodiments of the present application, the test method of the conductivity test is as follows: in an argon atmosphere, the powder of the solid electrolyte material of some embodiments and the comparative example is filled inside a pressurized mold. Inside the pressurized mold, a pressure of 500MPa is applied to the powder of the solid electrolyte material using upper and lower punches. Keeping the state of applying pressure unchanged, the upper part of the punch and the lower part of the punch are respectively connected to a constant potential instrument equipped with a frequency response analyzer, and the ionic conductivity of the solid electrolyte material is measured by the electrochemical impedance method. The real value of the impedance at the measuring point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the solid electrolyte material to ionic conduction.
[0160] In the embodiment of the present application, the test method of the all-solid-state battery test is as follows: in an argon atmosphere, Li is mixed in an agate mortar in a mass ratio of 30:70. 6 PS 5 Cl solid electrolyte material and positive electrode active material, namely LiCoO 2 These materials are mixed to obtain a positive electrode mixture. 3Li2 S.P. 2 S 5 yLiSCN (60 mg) and Li 6 PS 5 Cl solid electrolyte material (24 mg) was added to obtain a laminate. A pressure of 160 MPa was applied to the laminate to form a solid electrolyte layer. 6 PS 5 The positive electrode mixture (5 mg) was stacked on the Cl solid electrolyte layer to obtain a stack. A pressure of 360 MPa was applied to the stack to form a positive electrode. 2 S.P. 2 S 5 A metal Li foil (300 μm thick) is stacked on the solid electrolyte layer formed by yLiSCN to obtain a stack. A pressure of 5 MPa is applied to the stack to form a negative electrode. A current collector formed of stainless steel is arranged on the positive electrode and the negative electrode, and a current collector lead is installed on the current collector. Finally, an insulating hoop is used to block the inside of the insulating cylinder from the external atmosphere, and the inside of the cylinder is sealed to obtain an all-solid-state battery, such as Fig. 9 The battery was tested for electrochemical performance at 1C in the voltage range of 2.5-4.2V.
[0161] In the embodiment of the present application, the test method of Young's modulus test is: use ultrasonic late echo technology to measure the elastic modulus of the sample, using a 5MHz frequency transducer. For an isotropic solid medium, its longitudinal wave sound velocity CL and transverse wave sound velocity CS are determined by the density, elastic modulus and Poisson's ratio of the medium. By accurately measuring the longitudinal and transverse wave sound velocities of the medium, the elastic modulus of the medium can be calculated.
[0162] In the examples of the present application, the test data of the electrolyte obtained in the above examples and comparative examples are shown in Table 1. From the test data of Example 1, Example 2, Example 3, Comparative Example 1, and Comparative Example 2, it can be obtained that the value of y has an effect on 3Li 2 S.P. 2 S 5 yLiSCN has a significant effect. When y is within 0.1-0.55, the XRD spectrum 2θ=20° / 2θ=21° peak intensity ratio and ionic conductivity are within an acceptable range. When y is 0.05 or 0.6, the material properties are significantly changed, and the ionic conductivity also decreases significantly. Fig.11 and Fig.12As shown, the peak intensity of 2θ=21° attributable to the Li4PS4I phase (414I phase) increases significantly, which indicates that the chemical composition has deviated and is not suitable for obtaining a phase with high ionic conductivity. It can be seen from the test data of Example 1 and Comparative Example 3 that sufficient amorphization is an indispensable condition for preparing high ionic conductivity glass-ceramics. Otherwise, the Li4PS4I phase will mainly precipitate, and a material with an ionic conductivity two orders of magnitude lower will be obtained. It can be seen from the test data of Comparative Examples 4 and 5 that the appropriate high-temperature heat treatment temperature for crystallization is about 150°C. A high-conductivity crystalline phase cannot be precipitated at a lower temperature, and a Li4PS4I phase (such as Fig.13 As shown), the cycle performance of the all-solid-state battery is affected, resulting in a low retention rate; from the test data of Comparative Example 6, it can be obtained that conventional LiI doping / substitution can obtain high ionic conductivity, and the thio-LISICON phase ratio (as shown) Fig.14 As shown in Figure 3, it is impossible to take into account the low modulus at the same time, while the LiSCN doping / substitution with similar ionic radius and lower lattice energy shows unique advantages; it can be obtained from the test data of Example 3 that the use of LiSCN·H containing crystal water 2 O also has no effect on the purity and ionic conductivity of the final product, which may be related to the loss of water molecules during ball milling.
[0163] Table 1. Physical property test results of different samples and all-solid-state battery cycle performance
[0164]
[0165] As can be seen from the examples provided in the present application, the present application weighs Li and 2 S.P. 2 S 5 , LiSCN, to obtain a raw material for preparation; wherein the range of y is 0.1-0.55; placing the raw material for preparation, the dispersion medium and the ball milling ball in a ball milling jar for ball milling treatment to induce an amorphization reaction to obtain an intermediate product; wherein the ball milling speed corresponding to the ball milling treatment is 300-600rpm, and the ball milling time is 10-60h; heat treating the intermediate product to obtain the glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 ·yLiSCN. This application can prepare a glass ceramic solid electrolyte 3Li 2 S.P. 2 S 5 yLiSCN, which can maintain soft properties while taking into account high ionic conductivity, uses LiSCN as one of the raw materials, and the linear structure of SCN -It can be doped into the lattice to make the high-temperature fast ion conduction phase (high-temperature phase) more stable at room temperature, which relatively improves the room-temperature ionic conductivity of glass ceramics; LiSCN doped with 3Li 2 S.P. 2 S 5 The material maintains a lower Young's modulus, which helps to improve the density of the electrolyte isolation layer in the all-solid-state battery and effectively reduce the short-circuit risk of the battery at high current density; 3Li 2 S.P. 2 S 5 yLiSCN electrolyte has lower density, which helps to improve the energy density of all-solid-state batteries. In addition, there are no halogen atoms such as Cl / Br / I in the raw materials, which will not corrode the current collector. The raw materials are cheap and the heat treatment temperature is lower, which is conducive to large-scale production.
[0166] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a glass ceramic solid electrolyte, characterized in that: The method comprises: Li2S, P2S5 and LiSCN are weighed respectively according to a molar ratio of 3:1:y to obtain a preparation raw material; wherein the range of y is 0.1-0.55; The raw materials, dispersion medium and ball milling balls are placed in a ball milling jar for ball milling to induce an amorphization reaction to obtain an intermediate product; wherein the ball milling speed corresponding to the ball milling treatment is 300-600 rpm and the ball milling time is 10-60 hours; The intermediate product is heat treated at 60-200° C. for 1.1-55 h to obtain the glass ceramic solid electrolyte 3Li2S·P2S5·yLiSCN.
2. The method according to claim 1, characterized in that: The preparation raw materials, dispersion medium and ball milling balls are placed in a ball milling jar for ball milling to induce an amorphization reaction to obtain an intermediate product, including: The raw material, the dispersion medium and the ball milling balls are placed in the ball milling jar for ball milling treatment to induce the amorphization reaction, thereby obtaining a mixture of the ball milling balls and the intermediate product; the dispersion medium comprises one or more of saturated carbon chain hydrocarbons and benzene organic liquids; the mass ratio of the raw material, the dispersion medium and the ball milling balls is 1:(0-50):(1-50); The mixture of the ball milling balls and the intermediate product is separated to obtain the intermediate product.
3. The method according to claim 2, characterized in that The step of placing the preparation raw material, the dispersion medium and the ball milling balls in the ball milling jar for ball milling to initiate the amorphization reaction and obtain a mixture of the ball milling balls and the intermediate product comprises: Placing the preparation raw material, the dispersion medium and the ball milling balls in the ball milling jar for ball milling to initiate the amorphization reaction and obtain a mixture of the ball milling balls and the initial intermediate product; Using Cu-Kα line as X-ray source to test the initial intermediate product, and obtaining the test result of the initial intermediate product; If the test result of the initial intermediate product indicates that the initial intermediate product is amorphous, the initial intermediate product is determined to be an intermediate product, and a mixture of the ball milling balls and the intermediate product is obtained.
4. The method according to claim 1, characterized in that The intermediate product is subjected to heat treatment at 60-200° C. for 1.1-55 hours to obtain the glass ceramic solid electrolyte 3Li2S·P2S5·yLiSCN, comprising: The intermediate product is placed at a first preset temperature for a heat treatment to obtain an initial product; the first preset temperature range is 60-90° C., and the time corresponding to the heat treatment is 1-5 hours; The initial product is placed at a second preset temperature for secondary heat treatment to obtain the glass ceramic solid electrolyte; the second preset temperature range is 100-200° C., and the time corresponding to the secondary heat treatment is 0.1-50 hours.
5. The method according to claim 4, characterized in that The initial product is placed at a second preset temperature for secondary heat treatment to obtain the glass ceramic solid electrolyte 3Li2S·P2S5·yLiSCN, include: Placing the initial product at the second preset temperature for the secondary heat treatment to obtain the secondary heat treated product; Using Cu-Kα rays as an X-ray source to test the product of the secondary heat treatment to obtain a test result of the product of the secondary heat treatment; According to the test result of the product of the secondary heat treatment, it is determined whether the peaks of the product of the secondary heat treatment at 2θ=20° and 2θ=21° meet the preset conditions.
6. The method according to claim 5, characterized in that The step of determining whether the peaks of the product of the secondary heat treatment at 2θ=20° and 2θ=21° meet preset conditions according to the test result of the product of the secondary heat treatment comprises: If it is determined that the peaks of the product of the secondary heat treatment at 2θ=20° and 2θ=21° meet the preset conditions, then the product of the secondary heat treatment is determined to be the glass ceramic solid electrolyte; If it is determined that the peaks of the product of the secondary heat treatment at 2θ=20° and 2θ=21° do not meet the preset conditions, continue the secondary heat treatment until the peaks of the product at 2θ=20° and 2θ=21° meet the preset conditions.
7. The method according to claim 1, characterized in that The glass ceramic solid electrolyte 3Li2S·P2S5·yLiSCN is formed by stacking a plurality of spherical glass ceramic solid electrolyte particles, and the particle size of the glass ceramic solid electrolyte particles ranges from 0.5 to 3 μm; The glass ceramic solid electrolyte 3Li2S·P2S5·yLiSCN includes one or more of a glass state and a glass ceramic.
8. The method according to claim 1, characterized in that The glass ceramic solid electrolyte 3Li2S·P2S5·yLiSCN has a peak intensity ratio in the range of 1.65-2.05 at 2θ=20° / 2θ=21° in diffraction measurement using Cu-Kα line as an X-ray source.
9. A glass ceramic solid electrolyte, characterized in that: The glass ceramic solid electrolyte is prepared by the preparation method according to any one of claims 1 to 8.
10. An all-solid-state battery, characterized in that: The all-solid-state battery comprises a composite positive electrode layer, a composite negative electrode layer and an isolation layer; at least one of the composite positive electrode layer, the composite negative electrode layer and the isolation layer comprises the glass ceramic solid electrolyte as claimed in claim 9.
Citation Information
Patent Citations
Sulfide solid electrolyte materials, lithium solid-state batteries, and methods for preparing sulfide solid electrolyte materials
CN103650231B
Cited By
Solid-state electrolyte, solid-state electrolyte membrane and preparation method thereof, and solid-state battery
CN121905944A